Evolutionary model to guarantee quality of service for tactical worldwide interoperability for microwave access networks - Ravishankar Huchappa; Kiran Kumari Patil (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
The smart phone industries evolution had made the growth in wireless communication. The increase in social media usage led to huge increase of network traffic as sharing of data for multimedia like video conferencing, and voice over internet protocol (VoIP). Majority of services like this requires network resources and real-time strict quality of service (QoS). However high cost of network deployment is included. All the major service providers are currently being adopted to the WiMAX 802.16 network. Therefore, the worldwide interoperability for microwave access (WiMAX) network must have different supply policies and QoS for various applications. The implementation of these QoS policies was not provided by WiMAX for various needs of application. Recently development of various scheduling mechanism for QoS provisioning has been made. However, users improper synchronization made these models inefficient. To address this, uplink scheduling with feedback is considered to provision QoS. However, it induces delay in accessing slots, as result the bandwidth is wasted. To utilize bandwidth efficiently evolutionary computing is adopted by various existing model. However, these models induce computation overhead and may not be suitable for provisioning real-time services. The evolutionary computing model is used to compute ideal threshold.